Income tax and inequality in Brazil: The real “Income Transfer” - Rezende, Thiago Dutra Hollanda de (Argumentum, 2026)
“Income transfer” programmes have a significant impact on the lives of the poorest sectors of the working class, giving those who promote them a significant political advantage. This is the subject of debates and challenges regarding the fiscal impact of such measures. This article problematises this issue, employing political economy critique methodology, and fiscal and budgetary data. It seeks to demonstrate that a much more significant "Income Transfer" occurs through the benevolent taxation of the profits and capital gains of the wealthiest in Brazil, a topic that does not receive the same concerned coverage, hiding a tax structure that oppresses the poorest.
Keywords: Income tax; Brazilian tax system; Income transfer; Public fund; Inequality